Synthesis and Characterization of Electrodeposited C-PANI-Pd-Ni Composite Electrocatalyst for Methanol Oxidation. (16th October 2014) - Mahapatra, S. S.; Shekhar, S.; Thakur, B. K.; Priyadarshi, H.
Abstract : Electropolymerization of aniline at the graphite electrodes was achieved by potentiodynamic method. Electrodeposition of Pd (C-PANI-Pd) and Ni (C-PANI-Ni) and codeposition of Pd-Ni (C-PANI-Pd-Ni) microparticles into the polyaniline (PANI) film coated graphite (C-PANI) were carried out under galvanostatic control. The morphology and composition of the composite electrodes were obtained using scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDX) techniques. The electrochemical behavior and electrocatalytic activity of the electrode were characterized using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and chronoamperometric (CA) methods in acidic medium. The C-PANI-Pd-Ni electrode showed an improved catalytic performance towards methanol oxidation in terms of lower onset potential, higher anodic oxidation current, greater stability, lower activation energy, and lower charge transfer resistance. The enhanced electrocatalytic activity might be due to the greater permeability of C-PANI films for methanol molecules, better dispersion of Pd-Ni microparticles into the polymer matrixes, and the synergistic effects between the dispersed metal particles and their matrixes.